2009
DOI: 10.1007/s11998-009-9177-1
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of specific interactions to enhance the mechanical properties of polysiloxane coatings

Abstract: Moisture-curable polysiloxanes were modified with ionic groups to enable specific interactions between the polysiloxane matrix and silica nanoparticle reinforcement. A trimethoxysilane-functional quaternary ammonium salt (QAS) was used to modify the polysiloxane matrix. A comparison of the mechanical properties of coatings containing QAS modification to analogous coatings without QAS modification showed that QAS modification resulted in a dramatic improvement in mechanical properties of silica nanoparticlerein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In addition, the biomass that was retained was essentially completely removed by water-jetting. Majumdar et al also demonstrated that the modification of a polysiloxane matrix with QAS groups, coupled with the addition of silica nanoparticles, may provide a novel means for improving the toughness and durability of silicone FRCs. The ionic groups present in the PDMS-QAS matrix provide increased interfacial adhesion between the polymer matrix and silica particles, which is attributed to ion–dipole interactions involving silanol groups present on the silica surface.…”
Section: Hybrid Silicone-based Fouling Release Coatingsmentioning
confidence: 99%
“…In addition, the biomass that was retained was essentially completely removed by water-jetting. Majumdar et al also demonstrated that the modification of a polysiloxane matrix with QAS groups, coupled with the addition of silica nanoparticles, may provide a novel means for improving the toughness and durability of silicone FRCs. The ionic groups present in the PDMS-QAS matrix provide increased interfacial adhesion between the polymer matrix and silica particles, which is attributed to ion–dipole interactions involving silanol groups present on the silica surface.…”
Section: Hybrid Silicone-based Fouling Release Coatingsmentioning
confidence: 99%
“…Researchers at the Center for Nanoscale Science and Engineering of the North Dakota State University have also been using CHT methods to investigate polysiloxane-based coatings possessing tethered quaternary ammonium salt (QAS) groups for combating marine biofouling. The rationale for incorporating QAS groups into the polysiloxane matrix was based on the well-known inhibitory effect of QASs toward many microorganisms including Gram-positive and Gram-negative bacteria, yeasts, and molds. The positively charged nitrogen atom of QASs can bind to the negatively charged cell wall of a microorganism resulting in disruption of the integrity of the cell wall and, as a result, cell death. , By tethering QASs groups to the polymer matrix, it was thought that an antimicrobial effect could be obtained without causing harm to the environment, which is stark contrast to current antifouling coatings that function by releasing copious amounts of biocide into the ocean . The rationale for utilizing a polysiloxane-based coating was based on the good fouling-release properties previously observed for polysiloxanes .…”
Section: Materials Development Examplesmentioning
confidence: 99%
“…The finding that N-PEI doped PDMS shows a significantly higher protein adsorption than PDMS is not surprising, since the surface energy of this material is supposed to be higher than that of pure PDMS and should also contain positive charged patches. 39 The finding that the PEM films (except PDDA-PSS) no matter if positively, negatively charged, cross-linked or not exhibit lower or equal protein coverage than PDMS is quite surprising, since the surface energy of these films is higher than that of PDMS. 12 This effect is explained with the fact that all of these PE (polyelectrolytes) are not only electrostatically charged but also contain hydrophobic parts and therefore they experience micro-phase separation.…”
Section: Coomassie Blue Stainingmentioning
confidence: 99%